Removal of paraffin deposition using yeast - Radzali, Suria Riza (2007)
Paraffin deposition occurred when the Paraffin deposition occurred when the oil temperature falls below the oil temperature falls below the Wax Appearance Temperature Appearance Temperature These deposits generally consist of These deposits generally consist of straight and branched chain straight and branched chain hydrocarbons hydrocarbons.